White plague disease outbreak in a coral reef at Los Roques National Park, Venezuela - Croquer, Aldo (2003)
Coral diseases have been reported as a major problem affecting Caribbean coral reefs. During August 2000, a coral mortality event of White Plague Disease-II (WPD-II) was observed at Madrizqui Reef in Los Roques National Park, Venezuela. This disease was identified as the major cause of coral mortality, affecting 24% of all colonies surveyed (n = 1 439). Other diseases such as Black Band Disease (BBD), Yellow Blotch Disease (YBD), Dark Spots Disease (DSD) and White Band Disease (WBD) were also recorded, but showed a lower incidence (0.140.97%). Two depth intervals, D1 (5.5-6.5 m) and D2 (9-9.5 m) were surveyed with two sets of three band transects 50 x 2 m long, placed parallel to the long axis of the reef. All healthy and injured corals, along each band transect, were counted and identified to species level. Additionally, all diseases and recent mortality that were still identifiable on each colony also were recorded. The incidence of colonies affected by WPD-II ranged from 12.8 to 33% among transects, where thirteen species of scleractinian corals showed several degrees of mortality. The species most affected were Montastraea annularis (39.13%), M. faveolata (26.67%), M. franksi (9.86%), Stephanocoenia intersepta (7.25%), Colpophyllia natans (6.96%), Diploria labyrinthiformis (2.99%), Mycetophyllia aliciae (2.03%), M. cavernosa (1.74%), and D. strigosa (1.45%). WPD-II was more common in the deeper strata (9-9.5 m), where 63% of the surveyed colonies were affected, although the disease was present along the entire reef. Presently, it is imperative to determine how fast the disease is spreading across the reef, how the disease spreads across the affected colonies and what the long-term effects on the reef will be.